Storage Stability Analysis of Crude Amylase Extract from Banana Peel by Solid State Fermentation - Wakiah, Nurul; Fadillah, Ummu Farah; Sudirman, Sudirman; Riskawati, Riskawati (Jurnal Biologi Tropis, 2025)
Banana peel is a carbohydrate-rich by-product with potential as a fermentation substrate for enzyme production. This study aimed to evaluate the amylase production and storage stability of enzymes obtained through solid-state fermentation (SSF) of banana peel flour using Bacillus subtilis and Bacillus licheniformis. Fermentation was conducted for 24 and 48 hours, followed by crude enzyme extraction and storage for 24 hours at room temperature. Proximate analysis revealed banana peel flour contained 78.64% carbohydrates and 46.24% starch, supporting its suitability as a fermentation medium. The highest amylase activities were 50.36 IU/mL/min (B. subtilis) and 56.33 IU/mL/min (B. licheniformis) after 24 hours, with comparable values at 48 hours. However, enzyme activity declined by over 78% after 24 hours of storage, indicating low stability at room temperature. These findings confirm that banana peel flour is an effective, low-cost substrate for amylase production via SSF. Nevertheless, stabilization strategies post-fermentation are crucial to preserve enzyme activity during storage. This study highlights the dual benefit of converting agricultural waste into valuable enzymes and supports further research on improving enzyme shelf-life for industrial applications.